China’s accession to the port state measures agreement: contributions to conservation of marine biological resources, potential challenges and practical solutions - Qiyue, Zhang (Frontiers in Marine Science, 2025)
In April 2025, China acceded to the Agreement on Port State Measures, marking its active efforts in combating illegal, unreported, and unregulated fishing. This represents a significant initiative of China to protect the marine ecological environment, achieve sustainable development of fisheries, and deeply participate in global marine governance, while also indirectly responding to the constrains from the United States through its “Indo-Pacific Maritime Domain Awareness Partnership”. This manuscript employs dual perspectives from international relations and international law, along with research methods such as literature review, legal provision analysis, comparative analysis, and case study, to examine the positive impacts, risks, and challenges brought by China’s accession to the Agreement. The research result is that China’s accession to the Agreement enables it to enhance the effectiveness of combating IUU fishing, better protect marine biological resources and fishery resources, and is conducive to improving its international image. In order to better fulfill the international obligations, China needs to ensure the coordination of domestic laws such as the Fishery law with the Agreement, fulfill its responsibilities and obligations as a port State, flag State, and developing country, and strengthen port supervision and compliance capabilities. Meanwhile, China also faces risks such as insufficient law enforcement capacity and certain developed states’ discriminatory inspections against Chinese fishing vessels. The research concludes that China should coordinate domestic laws with the Agreement on Port State Measures and other relevant laws and regulations, complete the upgrading and transformation of its domestic fishery industry, fulfill its responsibilities as a port State, flag State, and contracting party, establish standardized law enforcement procedures, improve the capacity of supervision and law enforcement, enhance the institutionalization, informatization, and intelligentization of fishery management, and actively participate in regional and international fishery cooperation. This article further discusses the accession to the Agreement marks China’s transformation from a “rule adapter” to an “rule builder” in global fishery governance, providing a practical path for balancing domestic sustainable fishery development with participation in global governance and constructing a maritime community with a shared future.